Expressing Opinions with Verbal Irony on the Illegal Acts in the Case of Flares and Football Cheering:: A Pragmatics Study - Kavilanan, Siravast (Journal of Letters, 2024)
Verbal irony is a statement with an opposite meaning. This research aimed to study the characteristics and functions of verbal irony used to express opinions on the illegal acts in the case of flares and football cheering based on the pragmatics approach. Data was collected from June 25, 2023, to December 31, 2023. The analysis results revealed that the Facebook users used six types of verbal irony, namely contradictory adjacent expressions, echoic irony, irrational expressions, overly exaggerated expressions, inappropriate language, and comparison. These types of verbal irony were used to express sarcasm, tease, instruct, and criticize. It is the function of expressing negative feelings to allow the page admin to recognize bad feelings towards setting off flares at the stadium.